Digital Marketing and Impulse Purchasing in the Fast-Fashion Industry: Analysing Consumer Behaviour Through a Hedonic Lens - Ma, Emilie (2022)
With the fast-fashion industry quickly becoming one of the world’s top polluters, change is needed on an individual, societal, and institutional level. Further, with the invention of the internet and a large shift towards online shopping, especially in younger consumers, brands are using more resources to create effective digital marketing. As such, the purpose of this study is to explore how digital marketing influences impulse purchasing behaviours in consumers aged 18 to 30 years old. More specifically, this research aims to identify and understand the digital marketing tool that has the strongest positive influence on impulsive fast-fashion consumption, and how this tool can be used to encourage sustainable consumption. A qualitative study was undertaken to complete the research, with seven one-on-one interviews conducted to ensure rich data, and analysis was completed using a hedonic lens. The findings indicate that impulsive purchasing behaviour is an emotional and complex process, with post-purchase guilt often being justified through a number of avenues. Further, the data revealed that personalised digital marketing, and more specifically e-WOM that comes from social media influencers and celebrities, is the digital marketing tactic with the strongest positive influence on the specified consumer group. The findings also indicated that consumers are unwilling to invest in sustainable consumption due to perceived barriers of cost and lack of accessibility, however these barriers are often self-imposed to justify a continuation of impulse purchasing. To encourage sustainable consumption, digital marketing managers should prioritise and invest in targeted marketing that consumers will feel a connection to, such as identifying potential new consumers whose interests align with their brands. Further, marketing managers should utilise social media influencers and celebrities in campaigns that encourage sustainable consumption.